Quality blues: traditional knowledge used for natural indigo identification in southern China - Yuru Shi; Libin Zhang; Lu Wang; Shan Li; Zuchuan Qiu; Xiaoyong Ding; Yuhua Wang (BMC, 2021)
Abstract Background As one of the oldest traditional dyes, people worldwide have used natural indigo for centuries. Local people have unique knowledge about indigo identification, which is crucial for indigo quality control and determining the dyeing effects. However, such traditional knowledge is rarely documented and explained. Therefore, the aims of this study were to document and assess the traditional knowledge used by local people when identifying natural indigo paste as well as quantitatively explore the characteristics and material basis of such traditional knowledge. Method Three field surveys were conducted between 2019 and 2020. A total of 283 traditional indigo-paste artisans were interviewed in Guizhou, Yunnan, and Fujian Provinces. The frequency of citation, mention index, and fidelity level of each indigo-paste quality criterion were calculated to determine the most commonly used, recognized, and important quality criteria. To explore the characteristics and material basis of the traditional knowledge, we analyzed 21 indigo-paste samples using high-performance liquid chromatography with diode-array detection (HPLC-DAD), pH, and particle size analyses. Results Local people possess unique knowledge to identify natural indigo. Based on this knowledge accumulated over thousands of years, four criteria (color, taste, touch, and dyeing ability) were chosen by local people, and using these criteria, nature indigo was divided into five quality grades. The best quality indigo paste was judged according to the following folk criteria: dark blue in color with a purple-red luster; smooth and difficult to wipe off; having a sweet, bitter or spicy taste; and easy cloth dyeing. Additionally, the higher the contents of indigo and indirubin-especially indirubin-the better is the quality of the indigo paste. Within the pH range of 9-12, high-quality indigo-paste was more acidic. There was no significant relationship between particle size and quality. Conclusion The ancient methods used by local people for identifying natural indigo are comprehensive and unique. By documenting the various folk quality criteria and conducting quantitative analyses, this study revealed the importance of indirubin and pH for assessing the quality of indigo paste. These findings differ from existing quality standards for synthetic indigo. Amid rapid modernization, traditional knowledge remains invaluable as a world heritage of humanity that warrants preservation.